2021
DOI: 10.1177/1359104521994178
|View full text |Cite
|
Sign up to set email alerts
|

Therapist self-disclosure: Let’s tackle the elephant in the room

Abstract: Therapist Self-Disclosure (TSD), the revealing of a therapist’s feelings, thoughts or personal information to a client, is an inevitable aspect of therapeutic relationships. However, despite its prevalence in clinical settings, we believe there is insufficient recognition and exploration of TSD in our work with children and adolescents. Because TSD is not often formally addressed during training, therapists across the spectrum of clinical child psychology and psychiatry are often left with the belief that disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Similarly, it would be prudent for professionals to ensure they have built rapport with the youth in a sensitive but also developmentally appropriate way, rapport that will extend across meetings and encounters with the youth over months or years, especially with trafficked youth who may be particularly resistant when first working with professionals (Ahern et al, 2017;Farr et al, 2021). School professionals may want to consider strategies such as mutual sharing of information at the outset of interactions, which has been shown to enhance adolescents later disclosures of negative information (Dianiska et al, 2024), or other strategies evaluated and recommended in clinical or forensic interview settings designed to enhance youth reporting (e.g., Alfi-Yogev et al, 2021;Johnsen & Ding, 2021). Overall, insofar as school professionals can gain trust from vulnerable youth, training on how to ask the youth questions in a supportive and nonleading manner that elicits clear disclosures would be a significant and valuable addition.…”
Section: School Professionals' Knowledge and Trainingmentioning
confidence: 99%
“…Similarly, it would be prudent for professionals to ensure they have built rapport with the youth in a sensitive but also developmentally appropriate way, rapport that will extend across meetings and encounters with the youth over months or years, especially with trafficked youth who may be particularly resistant when first working with professionals (Ahern et al, 2017;Farr et al, 2021). School professionals may want to consider strategies such as mutual sharing of information at the outset of interactions, which has been shown to enhance adolescents later disclosures of negative information (Dianiska et al, 2024), or other strategies evaluated and recommended in clinical or forensic interview settings designed to enhance youth reporting (e.g., Alfi-Yogev et al, 2021;Johnsen & Ding, 2021). Overall, insofar as school professionals can gain trust from vulnerable youth, training on how to ask the youth questions in a supportive and nonleading manner that elicits clear disclosures would be a significant and valuable addition.…”
Section: School Professionals' Knowledge and Trainingmentioning
confidence: 99%
“…Additionally, research has found that Hearing Voices Network consumer-led support groups (which focus on recovery, coping, and shared identity) are beneficial for people experiencing psychosis, at least in part because they are led by people who understand what it means to experience psychosis (e.g., Longden et al, 2018). On the other hand, researchers and clinicians have highlighted the potential risks of disclosing lived experience (e.g., Faulkner & Basset, 2012; Henretty & Levitt, 2010; Johnsen & Ding, 2021; E. Lee, 2014), and so further research is needed to unpack the conditions under which such disclosure is likely to be helpful versus harmful for supporting client wellbeing.…”
Section: Proposed Pathways Through Which Identity Leadership Can Faci...mentioning
confidence: 99%